Pembaharuan Hukum Penyelenggaraan Rapat Umum Pemegang Saham Secara Elektronik Pada Perseroan Tertutup - Muninggar, Roro Ajeng; Anggraini, Anna Maria Tri (Jurnal Ilmiah Penegakan Hukum, 2024)
This paper aims to examine the legal reform of the implementation of e-GMS in Private Companies. The issue focused on the regulation of the implementation of the e-GMS of the Private Company and legal reform. The writing of this study uses normative legal methods, and qualitative descriptive analysis. The results of the study show that the regulation of the e-GMS of a Private Company is contained in Article 77 of PT Law, however, the technical implementation has not been regulated. The implementation of the e-GMS of a Private Company can adopt the provisions for the implementation of the e-GMS of a Public Company as stated in POJK No. 16/2020. Basically, the implementation of the e-GMS of a Private Company is valid as long as the implementation is in accordance with the Law and other related technical rules. The role of legal reform in the field of PT has been reflected by the issuance of POJK No. 16/2020 which regulates the implementation of e-GMS of Public Companies as a form of responsive legal theory, however, it needs to be optimized because legal reform is still needed in the field of PT, especially regarding the implementation of e-GMS in Private Companies.